Manajer Risiko : Peran Kepala MTS N 1 Kota Yogyakarta Dalam Pembelajaran Daring Masa Pandemi Covid-19 - Irwanto Irwanto; Zainal Arifin (Institut Agama Islam Negeri (IAIN) Curup, 2020)
The transition of the learning system from offline to online raises new problems at the teacher, the learning process is not optimal, and the process of understanding teachers who do not understand IT. The principal as the school manager must be wise and decisive in analysing issues of education management strategies in school management practices. This study aims to analyse the role of madrasa principal in online learning during the Covid-19 pandemic risk management perspective in MTs N 1 Yogyakarta City. This research uses a qualitative approach. Data collected through in-depth interviews and observation. The results showed that the principal of MTs N 1 Yogyakarta City as the Risk Manager had carried out three stages of risk management, first (1) risk assessment to identify online learning problems during the Covid-19 pandemic, (2) risk mitigation, to ease the burden on teachers and students in the learning process through the policy of providing internet quota subsidies for teachers and students who are unable and do not assign too many assignments to students, and (3) risk evaluation, to see the problems of the online learning process through reports or complaints from both teachers and students. The role of the madrasa head as a Risk Manager must be to minimize, even eliminate the risk or adverse effects of the learning process during the Covid-19 pandemic. Online learning policies, giving quota subsidies, and reducing school work as a form of action to reduce the risk of being stricken with Covid-19 and alleviate psychological burdens, especially for students.